Value benefit analysis software and its application in Bolu-Lake Abant Natural Park - Aytekin, Alper; Corbaci, Omer Lutfu (Molecular Diversity Preservation Int, 2008)
Value benefit analysis (VBA) is a psychometric instrument for finding the best compromise in forestry multiple-use planning, when the multiple objectives cannot be expressed in the same physical or monetary unit. It insures a systematic assessment of the consequences of proposed alternatives and thoroughly documents the decision process. The method leads to a ranking of alternatives based upon weighting of the objectives and evaluation of the contribution of each alternative to these objectives. The use of the method is illustrated with hypothetical data about Bolu-Lake Abant Natural Park (BLANP). In this study, in addition, computer software controlling the confidence was created. This software puts into practice the method proposed by Churchman and Ackoff, and determines the significance of the alternatives quickly and accurately.
Keywords: Value Benefit Analysis (Vba); Computer Software; Bolu-Lake Abant Natural Park (Blanp)